Characterization of the oxidative system on Castanea sativa Mill. in association with the ectomycorrhizal fungi Pisolithus tinctorius and Amanita muscaria during the early stages of contact - Baptista, Paula (2011)
Mycorrhizae are symbiotic associations between soil borne fungi and the root system of higher plants having a beneficial role on plant growth. The fungus receives carbon from plant, while the plant increased nutrient uptake mediated via the fungus. In agroforestry systems, most of the mycorrhizae belong to ectomycorrhizal (ECM) group being the mechanisms controlling its development poorly defined. During arbuscular mycorrhizal (AM) establishment, some evidences suggest that a temporal and spatial activation of different defence mechanisms by plants are activated. The present work pretends to assess the influence of ECM inoculation on the activity of antioxidant enzymes from roots of Castanea sativa Mill., during the early stages of contact. The experimental work was carried out in an “in vitro” system, established between two symbiotic associations: Castanea sativa Mill. / Pisolithus tinctorius and Castanea sativa Mill. / Amanita muscaria. In these systems, plants were harvested at different times of fungi contact. The levels of H2O2 and the activity of oxidative stress enzymes, namely catalase (EC 1.11.1.6), superoxide dismutase (EC 1.15.1.1) and ascorbate peroxidase (EC 1.11.1.11), were determined in roots. The results suggest that in the early stages of plant-ECM fungi interaction the oxidative metabolism could be involved, in a similar way as described for plant-AM interactions, where the plants produce enzymatic as well as non-enzymatic defence responses. Preliminary results will be presented and discussed in order to understand the effect of ectomycorrhizal fungi contact on oxidative stress enzyme activities of the host.